New Means to Risk-Priority-Number for System Improvement - Sorooshian, Shahryar (Romanian Society for Quality Assurance - SRAC, 2019)
Manufacturing could be an example of a typical system. Various manufacturing systems are reported to be failed because of the simultaneous onslaught of failure modes. The classic RPN (Risk Priority Number) formulation used in the failure mode and effects analysis was not successful to prevent the system failures and system improvements. Hence, this article proposes an improvement of the RPN formulation. The aim of the proposed formulation is to expand the RPN to a better system-oriented model. The proposed formulation is able to consider the manufacturing system with its several components in RPN calculation. This system-oriented formulation can reduce the classic RPN defects.